Leituras da memória de infância e de os da minha rua - Fernanda Karine Cordeiro Lima (2017)
The central objective of this work is analyzes through studies of Comparative Literature the works Childhood (1945), by Graciliano Ramos, and Those of my street (2007), by Ondjaki. The theme in question - the fictional self-biography of childhood - was based on studies supported by theoretical and critical approaches to the areas of Literature, History and Memories. So these narratives of memories were investigated through the confluence of autobiographical and fictional elements. In the first part of our study we rescued the historical and literary links between Brazil and Angola. Following, we explain the theoretical bases and the concepts that supported our investigation from topics that talked about: the pathways of memory and the phenomena and discourses related to memory; the “subjective jump” and the importance of the presence of the subject of the enunciation in the narrative; the literature related to the narratives of trauma (from a psychoanalytic and historical perspective) and related to memories narratives. In the critical reading chapter of the works, we analyze how the categories author-narrator-character, in both works of our research. In the following we investigate how individual memory - through each narrator-protagonist - helps the construction and resistance of a collective memory, observing aspects such as: time; spaces; fictionalization of orality; precursors of memories by means of the representation of the figure of the old people. Finally, we highlight, in addition to the similarities, we point out convergent and disparate elements between the two works, which can provide the confirme basis for the hypothesis: Those of my street can be perceived as a possible re-reading of Childhood. We believe that this project will may favor research from the perspective of comparative literature for an exchange of knowledge between Brazilian and Angolan literature.